PENYELESAIAN TERHADAP EKSEKUSI TANAH YANG DIJADIKAN JAMINAN KREDIT DI PERSEROAN TERBATAS PERMODALAN NASIONAL MADANI UNIT LAYANAN MODAL MIKRO (PT PNM ULaMM) SAMARINDA AKIBAT KREDIT MACET - Wahyuni Puspita Sari (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT The land is a guarantee that is often used in credit agreements. For the debtors, using the land as collateral will provide ease in getting credit at the Bank. As for creditors, land as collateral also benefits them, because if the debtor does not make his achievements, the creditor can execute the land. But it’s worth looking at how the procedures in the excution of the land are. Are those procedures consistent with the existing laws?In this study, the writer used a normative research method with a literature study. And to complete this study the author also had a few interviews. The approach to laws and regulations associated with it.The result of this study shows that there are some factors causing the crash of credit. One of the factors leading to the crash of credit is the absence of good faith from debtors. Completion of land execution at PT PNM ULaMM Segiri Samarinda Unit is carried out by selling collateral land under the hand and selling collateral land through auction. And the process of completing land execution at PT PNM UlaMM is in accordance with the applicable legislation.Keywords: Land Execution, Credit Guarantee, and Crash Credit.